2022
DOI: 10.3389/fimmu.2022.1051875
|View full text |Cite
|
Sign up to set email alerts
|

TriTECM: A tetrafunctional T-cell engaging antibody with built-in risk mitigation of cytokine release syndrome

Abstract: Harnessing the innate power of T cells for therapeutic benefit has seen many shortcomings due to cytotoxicity in the past, but still remains a very attractive mechanism of action for immune-modulating biotherapeutics. With the intent of expanding the therapeutic window for T-cell targeting biotherapeutics, we present an attenuated trispecific T-cell engager (TCE) combined with an anti- interleukin 6 receptor (IL-6R) binding moiety in order to modulate cytokine activity (TriTECM). Overshooting cytokine release,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Higher grade CRS is most often manageable but requires patient hospitalization and can be life-threatening for the patient [52][53][54] . Recent engineering strategies aim at decreasing CD3 binding domain affinities or designing conditionally active TCEs [55][56][57][58][59] . An alternative strategy to improve the safety profile of bispecific TCEs while keeping high antitumor activity is to selectively recruit highly cytotoxic T cell subsets such as γδ T cells rather than indiscriminately recruit all T cells (reviewed in 60,61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher grade CRS is most often manageable but requires patient hospitalization and can be life-threatening for the patient [52][53][54] . Recent engineering strategies aim at decreasing CD3 binding domain affinities or designing conditionally active TCEs [55][56][57][58][59] . An alternative strategy to improve the safety profile of bispecific TCEs while keeping high antitumor activity is to selectively recruit highly cytotoxic T cell subsets such as γδ T cells rather than indiscriminately recruit all T cells (reviewed in 60,61 ).…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, TriTECM antibodies inhibited simultaneously and dose-dependently EGFR and IL6R signaling pathways and triggered efficiently T cell activation and cytotoxicity against EGFR+ cells. In addition, TriTECM-mediated antitumor T cell activity was attenuated in comparison with EGFR/PD-L1/CD3 TsAb variants, indicating TriTECM potential as TCE with cytokine release modulator activity 90 .…”
Section: Challenges and Perspectivesmentioning
confidence: 98%
“…The first-in-class tetrafunctional T-cell engager was reported in 2022, in which a fourth arm containing an anti-IL-6 receptor (IL-6R) was added to an anti-EGFR x anti-PDL1 × anti-CD3 agent to modulate the activity of this cytokine and decrease cytokine release syndrome [ 23 ]. The authors showed attenuated IFN-γ production while maintaining sufficient T-cell-mediated cytotoxicity against cancer cells.…”
Section: Multispecific Engagers Binding T Cells In Cancer Immunotherapymentioning
confidence: 99%
“…The authors showed attenuated IFN-γ production while maintaining sufficient T-cell-mediated cytotoxicity against cancer cells. This new strategy has the ability to modulate cytokine storms, an unfortunate side effect often observed with T-cell immunotherapy, although the release of other proinflammatory cytokines still needs further investigation [ 23 ].…”
Section: Multispecific Engagers Binding T Cells In Cancer Immunotherapymentioning
confidence: 99%